A Two-Step Strategy for Fabrication of Biocompatible 3D Magnetically Responsive Photonic Crystals - Liu, Hui; Wang, Caiqin; Wang, Peixi; Liu, Nan; Du, Qingfeng (Frontiers in Chemistry, 2019)
Extremely stable and biocompatible 3D magnetically responsive photonic crystals (MRPCs) are successfully prepared. Classic hydrothermal synthesis was applyed for preparation of the Fe3O4@C core. And then, modified Stöber method was employed for synthesis of the different size of Fe3O4@C@SiO2. Different from the traditional magnetic nanoparticles, the highly negative charged superparamagnetic nanospheres (SMNs), i.e., the double-shell structure Fe3O4@C@SiO2 are capable of rapidly self-assembling into 3D MRPCs with full visible and various colors that can be periodically and reversibly tuned under different kinds external magnetic fields within 1s. The assembling behavior and mechanism of the 3D MRPCs under EMF were monitored and analyzed. The preparation is simple and the size of the SMN is easily controllable by adjusting the amount of catalyst. To conclude, our study provides an effectively two-step strategy for fabrication of biocompatible 3D MRPCs with the excellent long-term stability in aqueous solution and the highly charged surface features; and it reveals great potentials in biological fields.